Influence of conservation agricultural practices on performance of castor (Ricinus communis L.) based intercropping systems in shallow Alfisols under rainfed conditions: Influence of conservation agricultural practices on performance of castor (Ricinus communis L.) based intercropping systems in shallow Alfisols under rainfed conditions - G SURESH; AZIZ QURESHI (Journal of Oilseeds Research, 2020)
A fixed-plot field experiment was initiated during kharif 2018 to study the influence of conservation agricultural practices on performance of castor based intercropping systems in rainfed Alfisols. Different tillage practices (conventional tillage, reduced tillage and zero tillage) did not show significant influence on growth, yield attributes, seed yield and quality of castor. Seed yield of castor was significantly influenced due to different intercropping systems under the background of conservation agricultural practices. Sole castor recorded significantly higher castor seed yield (1064 kg/ha) followed by castor + groundnut (813 kg/ha); castor + greengram and castor + redgram (635 kg/ha).